The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/admi.201900677
|View full text |Cite
|
Sign up to set email alerts
|

The Topography of Silica Films Modulates Primary Macrophage Morphology and Function

Abstract: Macrophages are major contributors to the rejection of foreign materials introduced to living tissues. Given that cell‐surface interactions can have important effects on phagocytic capacity and cytokine production, changes in macrophage morphology have been reported for different materials and surface patterns. However, the details of how surface topography impacts morphology and function remain unclear. This study investigates whether changes in the surface topography of glassy substrates alter macrophage sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…The application of Fourier analysis for periodic feature size determination could be used to quantify how changes in material preparation parameters affect resulting properties including but not limited to elastic modulus, hydrophobicity or hydrophilicity, conductivity, adhesion, fouling, stretchability, and optical properties. Specifically, accurate characterization of periodic feature size could be applied to many areas of study including the extraction of mechanical moduli from buckled films; [15,16,22,23] assessment of how drying or crosslinking parameters affect the topography of wrinkled hydrogel systems; [43] analysis of cell growth, proliferation, and alignment as a function of surface topography; [44,45] quantification of the effect of structure size on anti-fouling properties; [26] and the characterization of current and resistance of stretchable electronics as a function of wrinkle size. [24]…”
Section: Fourier Analysis Of Thermally Structured Goldmentioning
confidence: 99%
“…The application of Fourier analysis for periodic feature size determination could be used to quantify how changes in material preparation parameters affect resulting properties including but not limited to elastic modulus, hydrophobicity or hydrophilicity, conductivity, adhesion, fouling, stretchability, and optical properties. Specifically, accurate characterization of periodic feature size could be applied to many areas of study including the extraction of mechanical moduli from buckled films; [15,16,22,23] assessment of how drying or crosslinking parameters affect the topography of wrinkled hydrogel systems; [43] analysis of cell growth, proliferation, and alignment as a function of surface topography; [44,45] quantification of the effect of structure size on anti-fouling properties; [26] and the characterization of current and resistance of stretchable electronics as a function of wrinkle size. [24]…”
Section: Fourier Analysis Of Thermally Structured Goldmentioning
confidence: 99%
“…Growing evidence has revealed that morphology is heavily associated with phenotype in certain macrophages; however, the phenomenon may not be universal. We and others have observed that while M2-polarized RAW264.7 exhibited well-spread cell shape, other macrophages did not display such dramatic changes [ 25 , 26 , 27 ]. Likely contributing to conflicting reports were several factors, including the differences between murine and human macrophages used in different reports, and the sensitivity of macrophages to different substrates including polymers, ceramics and metals [ 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 89%
“…It has been reported that topography design and size scale profile induce specific morphological cellular responses that can modulate macrophage activity [ 49 , 50 , 51 , 52 ]. Distinctive morphologies of primary human macrophages were observed on nano- and micro-textured PVDF surface with a correlation with inflammatory activity [ 16 ].…”
Section: Resultsmentioning
confidence: 99%